The Impact on Russia of WTO Accession and The Doha Agenda : The Importance of Liberalization of Barriers against Foreign Direct Investment in Services for Growth and Poverty Reduction - Rutherford, Thomas (World Bank, Washington, DC, 2012)
Taking price changes from the Global Trade Analysis Project (GTAP) model of world trade, the authors use a small open economy computable general equilibrium comparative static model of the Russian economy to assess the impact of global free trade and a successful completion of the Doha Agenda on the Russian economy, and especially on the poor. They compare those results with the impact of Russian accession to the World Trade Organization (WTO) on income distribution and the poor. The model incorporates all 55,000 households from the Russian Household Budget Survey as "real" households. Crucially, given the importance of foreign direct investment (FDI) liberalization as part of Russian WTO accession, the authors also include FDI and Dixit-Stiglitz endogenous productivity effects from liberalization of import barriers against goods and FDI in services. The authors estimate that Russian WTO accession in the medium run will result in gains averaged over all Russian households equal to 7.3 percent of Russian consumption (with a standard deviation of 2.2 percent of consumption), with virtually all households gaining. They find that global free trade would result in a weighted average gain to households in Russia of 0.2 percent of consumption, with a standard deviation of 0.2 percent of consumption, while a successful completion of the Doha Development Agenda would result in a weighted average gain to households of -0.3 percent of consumption (with a standard deviation of 0.2 percent of consumption). Russia, as a net food importer, loses from subsidy elimination, and the gains to Russia from tariff cuts in other countries are too small to offset these losses. The results strongly support the view that Russia's own liberalization is more important than improvements in market access as a result of reforms in tariffs or subsidies in the rest of the world. Foremost among the own reforms is liberalization of barriers against FDI in business services.